Subphrenic abscess due to Clostridium perfringens after hepatic resection for hepatocellular carcinoma following emphysematous cholecystitis: Report of a case. (2020) - Hamura, Ryoga; Haruki, Koichiro; Kumagai, Yu; Shiba, Hiroaki; Wakiyama, Shigeki; Yanaga, Katsuhiko
Highlights: Postoperative subphrenic abscess caused by Clostridium perfringens is rare after hepatic resection. Clostridium perfringens causes severe sepsis with high mortality rate. Early antibiotic and surgical treatment for the focus of infection is significantly improve in the survival rate. Abstract: Background: Subphrenic abscess caused by Clostridium perfringens is rare after hepatic resection. We herein report such a case after hepatic resection for hepatocellular carcinoma following treatment of emphysematous cholecystitis. Case presentation: A 69-years-old man with chronic hepatitis B, was admitted to our hospital for right subcostal pain and loss of appetite. Computed tomography (CT) revealed emphysematous cholecystitis, for which percutaneous transhepatic gallbladder drainage was performed. Clostridium perfringens was identified from the culture of the bile. Imaging studies immediately demonstrated hepatocellular carcinoma with right lobe of the liver, for which the patients underwent hepatic resection and cholecystectomy concomitantly. After operation, the patient developed emphysematous subphrenic abscess on postoperative day 15, for which CT-guided percutaneous drainage was performed. Clostridium perfringens was identified from the culture of the abscess fluid. The patient was given Ciprofloxacin and Clindamycin and made a satisfactory recovery. The patient was discharged on POD 95 and remains well with no evidence of tumor recurrence as of 8 years after resection. Conclusion: We herein reported a subphrenic abscess due to Clostridium perfringens after hepatic resection for hepatocellular carcinoma following emphysematous cholecystitis.